EXPLORATION OF NUTRACEUTICAL POTENTIAL OF HERBAL OIL FORMULATED FROM PARASITIC PLANT - Anjum, Fozia; Bukhari, Shazia Anwer; Shahid, Muhammad; Bokhari, Tanveer Hussain (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Cuscuta reflexa (C. reflexa) is a parasitic climber of medicinal importance. [pls state study objective]Materials and Methods: Hair formulations of C. reflexa collected from different host plants were prepared in the form of herbal oils (10% w/v). C. reflexa stems were extracted using mustard oil as base oil by using direct boiling technique. Prepared oil was studied as hair tonic. The experimental protocols used were anti-dandruff hair growth activity, as well as hair fall reduction. Herbal hair oils versus mustard oil were evaluated by applying oils on human volunteers with hair fall and dandruff problem whereas promotion of hair growth activity was conducted on rats. The formulated oils were also characterised for proximate analysis, physiochemical composition, as well as antimicrobial activity. Result: The test oils of C. reflexa collected from Azadiracta indica and Zizyphus jujuba were significantly effective in the promotion of hair growth, dandruff control, as well as reduction in hair fall activity. Conclusion: All the formulated oils showed potent antimicrobial activity against all selected strains of bacteria and fungi.